ALS biomarkers for therapy development: State of the field and future directions. Issue 2 (29th December 2015) - Benatar, Michael; Boylan, Kevin; Jeromin, Andreas; Rutkove, Seward B.; Berry, James; Atassi, Nazem; Bruijn, Lucie
ABSTRACT: Biomarkers have become the focus of intense research in the field of amyotrophic lateral sclerosis (ALS), with the hope that they might aid therapy development efforts. Notwithstanding the discovery of many candidate biomarkers, none have yet emerged as validated tools for drug development. In this review we present a nuanced view of biomarkers based on the perspective of the Food and Drug Administration; highlight the distinction between discovery and validation; describe existing and emerging resources; review leading biological fluid‐based, electrophysiological, and neuroimaging candidates relevant to therapy development efforts; discuss lessons learned from biomarker initiatives in related neurodegenerative diseases; and outline specific steps that we, as a field, might take to hasten the development and validation of biomarkers that will prove useful in enhancing efforts to develop effective treatments for ALS patients. Most important among these is the proposal to establish a federated ALS Biomarker Consortium in which all interested and willing stakeholders may participate with equal opportunity to contribute to the broader mission of biomarker development and validation. Muscle Nerve 53: 169–182, 2016